ANALYSIS LEGAL PROTECTION OF INSTRUMENTARY WITNESSES IN THE MAKING OF NOTARY ACTS (STUDY OF INDONESIAN NOTARY ASSOCIATION OF REGIONAL MANAGEMENT OF MEDAN CITY) - Rosnidar Sembiring; Zulfi Chairi; Ivana Novrinda Rambe (RADJA PUBLIKA, 2022)
The main purpose of this study is to analyze and examine the position and aspects of legal protection for instrumental witnesses in making a notarial deed. In giving his testimony at trial on a deed made by a Notary, the witness has an obligation to provide information with actual facts, if a witness submits false information, he can be punished according to the Criminal Procedure Code. The role of the instrumental witness is currently not getting enough attention from law enforcement even though an instrumental witness plays a major role in revealing a problem that arises as a result of legal actions from a Notary act. The Regional Board of the Indonesian Notary Association of North Sumatera often hears about several problems regarding instrumental witnesses in the practice of notary positions. The method used in this research is normative juridical. The nature of the research used in this research is descriptive analysis by describing the problem systematically and comprehensively. The purpose of descriptive analytical research is to describe accurately the nature of an individual, a symptom, a situation or a particular group. The data collection method used in this writing is using library research methods. To further develop this research data, an analysis was carried out directly to the informants using interview guidelines that had been prepared in advance. Interviews were conducted with the Chairperson of the Regional Board of the Indonesian Notary Association of North Sumatera to obtain facts in the practice of Notaries in Medan City regarding instrumental witnesses. The position of the instrumental witness in the Notary act is certainly different from the position of the witness in general, who is a witness who has heard and/or witnessed an event that has occurred. The position of the instrumental witness as one of the formal requirements of a Notary act is stated in Article 38 paragraph (4) letter c of the UUJN, that at the end or closing the deed must contain the full name, place and date of birth, occupation, position, position and residence of each witness. In accordance with Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, the legal protection provided for instrumental witnesses in making a Notary act in providing information is protected by the Witness and Victim Protection Agency (LPSK).